Clinical efficacy study of Qingre Huashi Yuyang formula combined with mesalazine entericcoated tablets in the treatment of damp-heat ulcerative colitis of large intestine: a randomized clinical trial - Hu Xiaojuan; Cheng Guobao; Yao Weijian; Zhang Jie; Xiao Yao; Cao Gan (结直肠肛门外科)
[Objectives] To explore the application value of Qingre Huashi Yuyang Formula combined with mesalazine enteric-coated tablets in the treatment of damp-heat ulcerative colitis of large intestine. [Methods] A total of 150 patients with damp-heat ulcerative colitis of large intestine admitted to Jiangsu Taixing People’s Hospital from June 2020 to June 2023 were enrolled and randomized into a control group (n＝75, treated with hormones or sulfasalazine combined with mesalazine enteric-coated tablets) and an observation group (n＝75, treated with Qingre Huashi Yuyang Formula in addition to the control group’s treatment). The clinical efficacy, colony counts of intestinal bifidobacterium and lactobacillus, incidence of adverse reactions, and modified Mayo scores, traditional Chinese medicine symptom scores, inflammatory indicators(serum endotoxin, also known as lipopolysaccharide, tumor necrosis factor-α, interleukin-6, prostaglandin E2), and immune indicators (D-lactic acid, interferon-γ) before and after treatment were compared between the two groups. [Results] The total effective rate in the observation group (94.7%) was higher than that in the control group (82.7%), and the incidence of adverse reactions (4%) was lower than that in the control group (13.3%), with statistically significant differences (P<0.05). Before treatment, there were no statistically significant differences in modified Mayo scores, traditional Chinese medicine symptom scores, levels of serum lipopolysaccharide, tumor necrosis factor-α, interleukin-6, prostaglandin E2, D-lactic acid, interferon-γ, and colony counts of intestinal bifidobacterium and lactobacillus between the two groups (P>0.05). After treatment, the modified Mayo scores, traditional Chinese medicine symptom scores, levels of serum lipopolysaccharide, tumor necrosis factor-α, interleukin-6, prostaglandin E2, D-lactic acid, and interferon-γ decreased in both groups, and the observation group showing lower levels than the control group, with statistically significant differences (P<0.05). Additionally, the colony counts of bifidobacterium and lactobacillus increased in both groups, with the observation group having higher counts than the control group, and the difference was statistically significant (P<0.05). [Conclusion] Qingre Huashi Yuyang Formula combined with mesalazine enteric-coated tablets is efficacious in the treatment of damp-heat ulcerative colitis of large intestine, effectively reducing intestinal inflammatory reactions, improving intestinal flora disorders, and exhibiting high safety, thus having clinical application and promotion value.